THE KALAR ANORTHOSITE-CHARNOKITE COMPLEX OF THE ALDAN-STANOVOI SHIELD: AGE AND TECTONIC IMPLICATIONS - Sal'nikova E.B.; Larin A.M.; Kotov A.B.; Glebovitskiǐ V.A.; Yakovleva S.Z.; Kovach V.P.; Berezhnaya N.G.; Tolkachev M.D.; Sukhanov M.K. (My University, 2004)
The new data considered characterize age of magmatic rocks from the Kalar Complex of the anorthosite-mangerite-charnokite-granite association (AMCG) in the junction zone of the Aldan shield and Dzhugdzhur-Stanovoi fold system. The U-Pb zircon dating showed that charnokite and gabbro of the complex are the Late Archean in age (2611 ± 38 and 2623 ± 23 Ma respectively) and experienced metamorphism of the granulite facies 1849 ± 15 Ma ago. An earlier granulite metamorphism (2627 ± 16 Ma) that predated the Kalar Complex emplacement was connected with collision between amalgamated terranes, which represent now the granulite basement of the Dzhugdzhur-Stanovoi fold system, and the Olekma-Aldan continental microplate. Accordingly, we suggest that the Kalar AMCG formed during the post-collision time. Based on dating results, we distinguished two AMCG associations of the Aldan-Stanovoi shield, which differ from each other in age and tectonic position. One association corresponds to the Late Archean post-collision plutons of the Kalar Complex, and the other one is represented by the Early Proterozoic (1.74-1.70 Ga) anorthosite massifs of the Dzhugdzhur Complex and by rocks of the Ulkan Complex, which are constituents of the Bilyakchan-Ulkan anorogenic volcano-plutonic belt.